Rocking-Sliding of a Rigid Block: Friction Influence on Free Motion - Andreaus, U.; Casini, P. (Engineering Transactions, 1998)
Many technical problems involve contact and impact between bodies. The contact problem is locally characterized by normal and shear forces; this contact may represent different types of phenomena such as rolling, sliding, impact and shock, unilateral contact, etc. The aim of this paper is to study the "contact-impact" problem of a rigid block colliding on a frictional base, by means of a numerical simulation, and to compare numerical results with analytical responses known from the literature. FVictional contact is taken into account by means of shear forces concentrated at a discrete number of points. Attention has been paid to two-dimensional free motion of the block with three degrees of freedom. Wide ranges of block slenderness and friction angle have been investigated and numerical results have been synthesized by means of the energy reduction ratio, which accounts for contact phenomena occurring during impact.